2019
DOI: 10.1111/aos.14102
|View full text |Cite
|
Sign up to set email alerts
|

Phacotrabeculectomy using collagen matrix implant (Ologen®) versus mitomycin C: a prospective randomized controlled trial

Abstract: Purpose: To compare the efficacy and safety of collagen matrix implant (Ologen â ; OLO) with mitomycin C (MMC) in phacotrabeculectomy. Methods: Prospective, single-centre, nonblinded, randomized controlled trial. A total of 53 eyes of 45 patients were enrolled in the study protocol with 27 eyes randomly assigned to OLO and 26 to MMC. The follow-up was 12 months. The primary outcome measure was mean change from baseline intraocular pressure (IOP) in both groups after 12 months. The secondary outcome measures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…The authors observed that bleb morphology, mean IOP, and medications at 1 year were comparable in the two groups. This is largely in agreement with the earlier studies[ 5 6 7 8 ] comparing collagen matrix and Mitomycin in phacotrabeculectomy published in other populations. In a prospective randomized control trial of phacotrabeculectomy using Collagen matrix or Mitomycin, Wlaz et al .…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The authors observed that bleb morphology, mean IOP, and medications at 1 year were comparable in the two groups. This is largely in agreement with the earlier studies[ 5 6 7 8 ] comparing collagen matrix and Mitomycin in phacotrabeculectomy published in other populations. In a prospective randomized control trial of phacotrabeculectomy using Collagen matrix or Mitomycin, Wlaz et al .…”
supporting
confidence: 92%
“…In a prospective randomized control trial of phacotrabeculectomy using Collagen matrix or Mitomycin, Wlaz et al . [ 7 ] had observed that the former provides similar surgical outcomes compared with Mitomycin and concluded it to be safe and effective alternative to Mitomycin for combined phacotrabeculectomy surgery. These results were in predominantly Caucasian eyes and may not necessarily be applicable across all ethnic groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found equal control of IOP at all time points with no inter group difference at 12 months which was similar to the results by Wlaz et al . [ 21 ] In contrast, Narayanaswamy et al . [ 22 ] found a greater percentage reduction of IOP in MMC group than in Ologen group at one year; however, IOP decrease at one year was not statistically different in the two groups, while Boey et al .…”
Section: Discussionmentioning
confidence: 99%
“…There was no intergroup difference in the mean number of medications at end point in our study, which was similar to that found by other authors. [ 13 21 ]…”
Section: Discussionmentioning
confidence: 99%